Prevalence of an inflammation and necrosis syndrome in suckling piglets. (8th January 2019) - Reiner, G.; Lechner, M.; Eisenack, A.; Kallenbach, K.; Rau, K.; Müller, S.; Fink-Gremmels, J.
Abstract : The current study describes the results obtained from clinical examination of over 4700 suckling piglets from 19 individual herds in Germany. In this cohort the prevalence of inflammation and necrosis in the tails, ears, claw coronary bands, heels and teats was determined using a pre-defined scoring system. Results show that already in the 1 st days of life, piglets were affected by inflammation and necrosis of the heels (80%), claw coronary bands (50%) and tail base (20%). The praevalences of these alterations in piglets were influenced by genetics ( P <0.001) and age, decreasing gradually in the 2 nd week of life ( P <0.001). Moreover, a correlation between tail length after tail docking and the prevalence of tail necrosis ( P ⩽0.04) was found. Tail and ear biting as a behavioural trait was not detected during this study. The early onset, appearance and multiple locations of clinical signs of inflammation and the positive correlation with the genetic background of the piglets may suggest an impairment of the innate immune system by infectious and non-infectious agents. This is in contrast to previously described behavioural abnormalities seen in fattening pigs. Considering the obvious reduction of animal welfare due to the described lesions, there is a need to create awareness among pig farmers and to understand the multifactorial causality involved in this inflammation and necrosis syndrome in piglets.